2010
DOI: 10.1016/j.ijid.2009.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up standard agglutination and 2-mercaptoethanol tests in 175 clinically cured cases of human brucellosis

Abstract: SAT and 2-ME may be found in significant titers in less than 5% of clinically treated cases after two years. Serologic cure for both tests with lower titers were higher than with higher titers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 17 publications
(23 reference statements)
2
25
0
2
Order By: Relevance
“…However, extended serological follow-up periods might not be reasonable in patients who are clinically well. Significant SAT titers are found in 3-5% of the clinically cured brucellosis cases 2 years after successful antibiotic treatment [69], and these figures may be even higher in different populations, after another antibiotic regimen, using other serological tests, and so on. …”
mentioning
confidence: 99%
“…However, extended serological follow-up periods might not be reasonable in patients who are clinically well. Significant SAT titers are found in 3-5% of the clinically cured brucellosis cases 2 years after successful antibiotic treatment [69], and these figures may be even higher in different populations, after another antibiotic regimen, using other serological tests, and so on. …”
mentioning
confidence: 99%
“…Therefore, another reliable test is needed for the diagnosis and follow-up of all patients with brucellosis. [23][24][25] SAT false-negative results may have occurred in patients with very recent infection or chronic cases. [26][27][28] With regard to the molecular method, we evaluated useful nested PCR assay for the diagnosis of human brucellosis in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This issue neither indicates that clinical recovery relating to the eradication of the organism nor stresses the point that the presence of DNA may be representing an active disease that requires treatment. 24,26 Hence, bacterial DNA persists in the blood of several patients throughout treatment and follow-up in those with significant clinical recovery. 13,14 One of the main characteristics of brucellosis is its noticeable tendency to relapse after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in endemic areas with more patients suffering from acute bacteremia, the SAT titer threshold is of at least 1:320 (47). As SAT in the chronic form has sometimes false-negative results, several studies have showed that in the first few days of the disease, even bacteremic patients had an SAT titer ≤ 1:160 (48).…”
Section: Satmentioning
confidence: 99%
“…In some studies, patients surveyed by PCR, after accomplishment of their treatment, have evidenced the bacteria in blood for a partly longer term brings into discussion the possibility of relapse (76). Relapse usually occurs within 6 months after cessation of treatment (47). Consequently, patients must pursue a treatment plan for 12 months.…”
Section: Pcrmentioning
confidence: 99%